(untitled) (Oxford)
This remains a most significant work, essential reading for those who wish to understand the workings of the present-day Japanese economy. It may be added that the translation is excellent, and the book can be read with pleasure as well as profit. Malcolm Falkus, Business History
Keywords: Finance,Industrial relations,Industrial policy,Japan,Japan; History,History,History,Economic conditions,Economic policy; 1918-1945; Japan,Japan,Japan